Cognitive Learning Theory and Its Application in Learning Islamic Religious Education at SMK Muhmmadiyah 1 Sumedang - Sundari, Susan; Tarsono, Tarsono (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Cognitive theory is an important aspect of educational theory, but it is nevertheless misunderstood by some educators. Interestingly, by the beginning of the 15th century, Muslim scholars had begun to emphasize the importance of returning to Islamic teachings based on the Quran and Hadith. It could be that modern theories of learning are rooted in these Islamic teachings or at least have equivalents that can be found. By examining the theoretical concepts of cognitive learning through the lens of Islamic education, this study aims to compare and distinguish Western concepts from those sourced from the Qur'an and Hadith. The research methodology used is literature research, which involves searching for in-depth literature on cognitive learning theory and Islamic education. From the point of view of Islamic education, the findings of this study show that cognitive theory must prioritize the development of students' thinking abilities while still paying attention to their physical and psychological growth. In addition, the study emphasizes that the process of transmitting knowledge is integral, and educators hold an important responsibility in facilitating the cognitive expansion of their students.